EDUCATION AND COMMUNITY DEVELOPMENT FOR SUSTAINABILITY: THE CONTINUATION OF THE LOY KRATHONG TRADITION OF BERK PHRAI SUB-DISTRICT, CHOM BUENG DISTRICT, RATCHABURI PROVINCE - Charoenlak, Nipawan (Journal of MCU Nakhondhat, 2023)
This academic article presents the findings on the Education and Community Development for Sustainability: The continuation of the Loi Krathong tradition of Berk Phrai Sub-District Chom Bueng District, Ratchaburi Province. In the study of local communities, it is a process of studying the nature of grassroots societies in order to understand the nature of the way of life of members of the community. By carrying on the local culture through the Loi Krathong tradition of Berk Phrai Subdistrict, Chom Bueng District, Ratchaburi Province At present, Berk Phrai Subdistrict, Chom Bueng District, Ratchaburi Province In order for sustainable development to occur, at least 2 issues must be taken: the balance of the environment, society and economy must be considered in developing and improving the quality of life and to promote the concept of fairness between women and men Fair and Peaceful Society Human Rights Environmental Conservation and Restoration multicultural and poverty alleviation. In the content of this article, we collect the inheritance of community culture by using traditions and cultures as the basis for developing and managing education to develop local communities towards sustainability such as: 1) collaborate with local educational institutions, 2) support, promote and facilitate community members to learn, 3) manage local cultural knowledge to provide knowledge to the community, 4) develop activities to promote lifelong learning, and 5) support community organizations to carry out public activities in the community. It can be regarded as a local culture that has a unique cost and a way of being Thai. The government sector and various agencies should preserve, inherit, and create in order to co-exist with Thai society. It is an incubator for communities and society to live happily. Including giving importance to the potential and needs of the area. to achieve real results for the community.